Response to resistance exercise performed in water vs. on land - Colado, J. C.; Tella, V.; Llop, F. (Biomechanics and Medicine in Swimming X, 2006)
The objective of the study was to verify if the cardiovascular and metabolic demands of well-designed water resistance training are at least comparable to their land-based equivalents. Five trained men were evaluated similarly with a horizontal shoulder adduction movement in water with a Hydro-Bells and on land with an elastic band (EB). Previously in order to equate resistance of movement, a rhythm rate in water and on land was established as well as distance in the holding distance of the EB. Subsequently physiologic response was evaluated with both devices by means of a set of twenty-five repetitions until reaching muscular fatigue. The results showed that there were no statistically significant differences between both material resources concerning heart rate at exertion and the response of lactates. We conclude that if the resistance training in water is performed according to the methodological indications followed in this study will produce a similar physiological response to that produced by land-based exercise.